Printer Friendly

Gauss and the regular heptodecagon.

Abstract. -- This note outlines the proof and provides a set of diagrams for the division of a circle into 17 equal arcs.

**********

Karl Friedrich Gauss (1777-1855) at the age of 18 gave a ruler-compass construction of dividing a circle into 17 equal arcs. This note consists of an outline of his proof and a set of diagrams which systematically give the construction.

QUADRATIC EQUATIONS

Let

a[x.sup.2] + bx + c = 0, a [not equal to] 0 (1)

be a quadratic equation with real coefficients. Consider a rectangular coordinate system (Fig. 1). Let A and B, on the x - axis, correspond to [x.sub.1] and [x.sub.2], respectively, where [x.sub.1] and [x.sub.2] are the roots of (1). Let OU = 1 and OD = c/a. Then

(OU) (OD) = c/a = [x.sub.1][x.sub.2] = (OA) (OB). (2)

This implies that the four points, U, D, A and B are on circle (1). Since M, the midpoint of AB, corresponds to

[1/2] ([x.sub.1] + [x.sub.2]) = [-b]/[2a], (3)

one can construct the circle which passes through U, D, A and B. Therefore the roots of (1) can be constructed (Amir-Moez 1987).

THE SEVENTEEN ROOTS OF UNITY

Consider the equation

[z.sup.17] - 1 = 0. (4)

[FIGURE 1 OMITTED]

One can easily factor (4) into

(z - 1)([z.sup.16] + [z.sup.15] + ... + [z.sup.2] + z + 1) = 0 (5)

Let [z.sub.0] = 1 and [z.sub.1] = z (Fig. 2). Observe that

[z.sub.k] = [z.sup.k], k = 1,..., 16 (6)

and

[z.sub.k] = [z*.sub.17 - k], k = 9,..., 16 (7)

[FIGURE 2 OMITTED]

where, for example, z* is conjugate of z. This implies that

[z.sub.h] + [z*.sub.17 - h] = 2 cos[[2([pi] + h[pi])]/17]. (8)

Then

[z.sub.h] = [x.sub.h] + i[y.sub.h] (9)

and

[z.sub.h] + [z*.sub.17 - h] = 2[x.sub.h], h = 9,..., 16. (10)

One can write (10) as:

[z.sub.k] + [z*.sub.17 - k] = 2[x.sub.h], k = 1,..., 8. (11)

(Dickson 1952).

[FIGURE 3 OMITTED]

THE RULER-COMPASS CONSTRUCTION

Gauss has considered

[l.sub.1] = [1/2] {(z + [z.sup.16]) + ([z.sup.2] + [z.sup.15]) + ([z.sup.4] + [z.sup.13]) + ([z.sup.8] + [z.sup.9])} = [x.sub.1] + [x.sub.2] + [x.sub.4] + [x.sub.8] (12)

and

[l.sub.2] = [1/2] {([z.sup.3] + [z.sup.14]) + ([z.sup.5] + [z.sup.12]) + ([z.sup.6] + [z.sup.11]) + ([z.sup.7] + [z.sup.10])} = [x.sub.3] + [x.sub.5] + [x.sub.6] + [x.sub.7] (13)

Note that

[l.sub.1] + [l.sub.2] = - [1/2], [l.sub.1][l.sub.2] = -1. (14)

[FIGURE 4 OMITTED]

Thus [l.sub.1] and [l.sub.2] satisfy the quadratic equation

[l.sup.2] + [1/2] l - 1 = 0. (15)

One can construct the roots of (15) (Fig. 3).

Next let

[m.sub.1] = [1/2] [(z + [z.sup.16]) + ([z.sup.4] + [z.sup.13])] = [x.sub.1] + [x.sub.4] > 0, (16)

and

[m.sub.2] = [1/2] [([z.sup.2] + [z.sup.15]) + ([z.sup.8] + [z.sup.9])] = [x.sub.2] + [x.sub.8], (17)

[m.sub.1] + [m.sub.2] = [x.sub.1] + [x.sub.2] + [x.sub.4] + [x.sub.8] = [l.sub.1], (18)

and

[m.sub.1][m.sub.2] = - [1/4]. (19)

[FIGURE 5 OMITTED]

So [m.sub.1] and [m.sub.2] satisfy the quadratic equation

[m.sup.2] - [l.sub.1]m - [1/4] = 0. (20)

By carrying [l.sub.1] from (Fig. 3), [m.sub.1] and [m.sub.2] can be constructed (Fig. 4). The reader may examine the figure against Figures 1 and 3.

Now

[n.sub.1] = [1/2] [([z.sup.3] + [z.sup.14]) + ([z.sup.5] + [z.sup.12])] = [x.sub.3] + [x.sub.5], (21)

and

[n.sub.2] = [1/2] [([z.sup.6] + [z.sup.11]) + ([z.sup.7] + [z.sup.10])] = [x.sub.6] + [x.sub.7]. (22)

Note that

[n.sub.1] + [n.sub.2] = [x.sub.3] + [x.sub.5] + [x.sub.6] + [x.sub.7] = [l.sub.2], and [n.sub.1][n.sub.2] = - [1/4]. (23)

[FIGURE 6 OMITTED]

Therefore [n.sub.1] and [n.sub.2] satisfy the quadratic equation

[n.sup.2] - [l.sub.2]n - [1/4] = 0. (24)

Constructing the roots of (24), one obtains (Fig. 5).

Finally note that

[x.sub.1] = [1/2] (z + [z.sup.16]) and [x.sub.4] = [1/2]([z.sup.4] + [z.sup.13]). (25)

So

[x.sub.1] + [x.sub.4] = [1/2] (z + [z.sup.4] + [z.sup.13] + [z.sup.16]) = [m.sub.1] (26)

and

[x.sub.1][x.sub.4] = [1/4]([z.sup.5] + [z.sup.14] + [z.sup.3] + [z.sup.12]) = [1/2][n.sub.1]. (27)

Therefore [x.sub.1] and [x.sub.4] satisfy the quadratic equation

[x.sup.2] - [m.sub.1]x + [1/4][n.sub.1] = 0. (28)

Constructing roots of (28) gives the final result (Fig. 6). Note that z and [z.sup.4] can be obtained from [x.sub.1] and [x.sub.4]. The rest of the construction is quite clear.

LITERATURE CITED

Amir-Moez, A. R. 1987. Gauss and the Regular Pentagon, School of Science and Mathematics 87(4), pp. 293-301.

Dickson, L. E. 1952. New First Course in the Theory of Equations, John Wiley and Son, Inc., New York, p. 163.

Ali R. Amir-Moez

Department of Mathematics

Texas Tech University, Box 4319

Lubbock, Texas 79409
COPYRIGHT 1998 Texas Academy of Science
No portion of this article can be reproduced without the express written permission from the copyright holder.
Copyright 1998 Gale, Cengage Learning. All rights reserved.

Article Details
Printer friendly Cite/link Email Feedback
Author:Amir-Moez, Ali R.
Publication:The Texas Journal of Science
Date:Aug 1, 1998
Words:946
Previous Article:Foraging flights, reproductive success and organochlorine contaminants in Cattle Egrets nesting in a residential area of Bryan, Texas.
Next Article:Chromosomal variation in the scrub mouse Akodon molinae (Rodentia: Sigmodontinae) in central Argentina.
Topics:

Terms of use | Privacy policy | Copyright © 2019 Farlex, Inc. | Feedback | For webmasters